DISTRIBUSI GLOTAL STOP BAHASA TOMBULU YANG DITUTURKAN DI KELURAHAN RURUKAN, PASLATEN, DAN TALETE KECAMATAN TOMOHON TIMUR - Wongkar, Yessy Hanna; Imbang, Djeinnie; Kalangi, Leika Maria Victoria (Universitas Sam Ratulangi, 2017)
This article was to describe the distribution of glottal stop in Tombulu language uttered in East Tomohon Sub-District. Four theories were chosen to be applied in this research. In various languages, glottal stops are said to occur within the following positions; Initial: in the vocal initial position, medial: between two vocals, and on intervocalic or at the morphemes boundary, final: at the vocal final position. The same theories were used to identify the distribution of glottal stops in Tombulu language. This was a qualitative research using a descriptive method. The techniques used for collecting data were observation, interview, recording, transcription and translation. The subjects of the research were the people who lived in the three villages mentioned above. The participants were chosen carefully based on some requirements, such as; mature enough, originally from Tomohon, living there, and possessing a complete set of articulators. It was found out that the glottal stop in Tombulu language occurs unpredictively. It could appear at the initial, medial, or final position within a word. Another interesting fact about the glottal distribution in Tombulu language was also found. It was found at the final particular prefixes, ma’- and pKeywords: Phonology, Consonant, Glottal stop